2021
DOI: 10.1111/fire.12280
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in MD&A section tone predict investment behavior?

Abstract: We find that changes in managerial tone predict firm corporate investment activities. Tone changes within the Management Discussion and Analysis section of the 10-K are positively related to subsequent capital investments and M&A activity. We find the predictive content of tone changes to be present at the firm and industry-levels, and when accounting for alternative sources of incremental information associated with firm investment activities. Our findings broaden the scope of information encapsulated by chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…Similarly, Berns et al (2022) find that an incremental positive tone, expressed from management discussion and analysis, that captures managerial sentiment is associated with subsequent corporate investments. Furtherly, a piece of Yuan et al's (2022) studies show that companies with more positive word usage in the annual report are prone to display higher research and development (R&D) expenditures in the subsequent year.…”
Section: Managerial Sentiment and Corporate Risk-takingmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, Berns et al (2022) find that an incremental positive tone, expressed from management discussion and analysis, that captures managerial sentiment is associated with subsequent corporate investments. Furtherly, a piece of Yuan et al's (2022) studies show that companies with more positive word usage in the annual report are prone to display higher research and development (R&D) expenditures in the subsequent year.…”
Section: Managerial Sentiment and Corporate Risk-takingmentioning
confidence: 86%
“…Whereas textual-based managerial sentiment is likely to overcome this limitation. As suggested by prior studies, positive and negative semantic words used in corporate disclosure reflect managerial positive bias, such as overconfidence (Liu and Nguyen, 2020), narcissistic trait (Bassyouny et al , 2020) and optimism (Jiang et al , 2019; Berns et al , 2022). Moreover, sentiment as a belief (Hsiao et al , 2014; Hribar et al , 2017) varies with time and events.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While not addressing the role of information directly, this strand of research centres on the role of the information flows. Similarly, the role of insider trading (Davis et al, 2021) and the tone of information release (Berns et al, 2022) have been given significant attention by researchers. Information flows have remained one of the important aspects of M&A research, and exploration should continue in this direction in the future.…”
Section: Frontier #1: Corporate Culture and Mergersmentioning
confidence: 99%
“…This section includes further explanations of important events in the earning calendar and descriptions of business plans, possible challenges and difficulties in the next year. Existing literature has suggested that when listed companies are trapped in financial trouble in the current year, the appearance of negative words in the MD&A section will increase, along with the level of uncertainty [33,34]. By analyzing the tone of earning calendars some researchers predicted the financial crisis of listed companies and verified the availability of non-standardized financial information in financial crisis recognition [35][36][37][38].…”
Section: The Emotional Tone Of Text and Financial Crisis Early Warningmentioning
confidence: 99%